Uma solução semi-analítica para a modelagem do bulbo molhado na irrigação por gotejamento superficial - Gomes, Jeovanizélio Firmino (2009)
The knowledge of the characteristics and dimensions of wetted bulb is substantially important in the measured of the drip irrigation. Due to the complexity of the physical phenomena involved in the infiltration and redistribution process of water in the soil, develop a mathematical model that simulates the flow of water in the soil is not a very simple task. The objective of this work was developed a mathematical model semi-analytic for predicting dimensions of wetted bulb that it depends on parameters of easy obtaining in the field, just as, the superficial diameter of the wetted bulb. The model allows the simulation of the format and dimensions of the wetted bulb for three different forms: when the diameter of the bulb is given in two depths of easy obtaining in the field, that is, in the surface of the soil and in the depth of 10 cm; starting from the superficial diameter and standards existent for the maximum depth in agreement with the texture of the soil; starting from the surfaces of answers. The mathematical model was obtained by numeric simulation of the equations that govern the flow of water in the soil, originating like this, semi-analytic solution for the formation of the wetted bulb. The model was validate, starting from field data of a soil with medium texture after compared with the simulate data. The accomplished comparisons demonstrate that the proposed model predicting the dimensions of the wetted bulb satisfactorily and it can be used as auxiliary tool in the measurement of the drip irrigation.